After progress: Experiments in the revaluation of values. Issue 2 (March 2022) - Savransky, Martin; Lundy, Craig
What might it take to learn to think and live after progress? The notion of 'progress' is arguably the defining idea of modernity: a civilisational imagery of a boundless, linear and upwards trajectory towards a future that, guided by reason and technology, will be 'better' than the present. It was this notion that placed techno-science at the heart of the modern political culture, and it was the global unevenness of 'progress' that imagined European imperialism as a civilising mission inflicted upon 'backward' others for their own sake. Whilst during the postcolonial era the modern idea of progress and its deleterious consequences on a global scale have deservingly been the object of fierce criticism, 'progress', its promises and its discontents still command global political imaginations, values and policies to this day. In the wake of its devastating social, political and ecological effects, this article argues that the imperative of progress is now one we cannot live with but do not know how to live without. Thinking of progress not as one modern value among others but as the very mode of evaluation from which modern values are derived, this article provides an introductory exploration of the question of what thinking and living after progress might mean. It also provides an overview of the many contributions that compose this monograph, as divergent experiments in the radical revaluation of our values.